Synthesis and characterization of heterocyclic compounds and modified amino acids with application in nonlinear optics and/or as fluorimetric and colorimetric sensors for anions and cations - Batista, Rosa Maria Ferreira (2011)
Tese de doutoramento em Ciências (área de especialização em Química)